PRANATA KELUARGA SEBAGAI AWAL PEMBENTUK KARAKTER ANAK - Zuri Astari (Samawa (Sakinah, Mawaddah Warahmah), 2023)
Every child is born from a different family background. Family is the main factor in shaping children's character. Children will learn and get their first education from the family environment, especially from the father and mother. Family institutions play a role as the initial foundation for the formation of children's character before entering the school environment and society. The goal is to teach and educate children according to religious teachings and applicable norms. This type of research uses library research. Data obtained from library research (library research) which comes from literature and other documentation materials. The data collection technique used by this researcher was a literature study, namely by finding data related to the discussion in the title of the research that the researcher took. The data analysis technique in this study used qualitative analysis techniques in a deductive way. The results of his research are introducing Allah SWT. to children as early as possible, avoid bad or impolite words in front of children, accustom children to telling honest words, set an example for children in maintaining trust, listen to children's criticism and reprimands, do justice, spend time with children, invite children to take every knowledge wherever he is.